Epidemiologic Trends in Cesarean Section Delivery in Hamadan Province during 1998-2019 using Joinpoint Regression Analysis - Salman Khazaei; Ensiyeh Jenabi; Ghodratollah Roshanaei; Samereh Ghelichkhani; Leyla Khazaei (Hamadan University of Medical Sciences, 2024)
Background and Objective: Due to the growing trend of the cesarean section rate in Iran in the past years, the natural childbirth promotion program was implemented as one of the health system transformation plans in 2014. The present study aimed to assess the trend of changes in the percentage of cesarean deliveries following the implementation of this program in Hamadan province. Materials and Methods: This longitudinal study was conducted using secondary data to investigate the changes in the rate of cesarean delivery during 22 years. The data required for this study included deliveries from April 1998 to March 2019 by delivery type. The statistical analysis of this study was performed in joinpoint software (version 3.4) using the joining point regression method. Results: The percentage of cesarean deliveries in the whole province during the study period has constantly increased, from 32% in 2017 to 48% in 2019. The results of the joinpoint regression indicated an annual increase of 1.9% in the trend of cesarean section in Hamadan province. The trend has some joinpoints, none of which correspond to the timing of the implementation of the health evolution plan. Conclusion: Based on the obtained results, although the transformation plan has been able to reduce the increasing percentage of cesarean births, this amount of change was not sufficient to achieve the predetermined goals of the health transformation plan.